10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
BACKGROUND: Postnatal care (PNC) is essential for reducing maternal and neonatal morbidity and mortality, especially in countries like India, where healthcare inequities persist. This study investigates the use and determinants of quality postnatal care (QPNC) in India, using Andersen's Behavioral Model of Health Services Utilization. QPNC in this study refers to the receipt of recommended skilled, timely, and appropriate PNC components. METHODS: The study used data from the National Family Health Survey (NFHS)-5, comprising 163,893 mother-newborn pairs. QPNC was operationalised using three dimensions: skilled care by qualified providers, timely first postnatal check-up within 24 hours, and receipt of essential postnatal interventions (e.g., cord examination, breastfeeding counselling, and other essential interventions). Multivariable logistic regression was applied to identify determinants of QPNC uptake, and secondary analyses examined determinants of each individual QPNC dimension. RESULTS: Only 49.8% of mother-newborn dyads received complete QPNC. Although 77.8% of mothers and 82.1% of newborns received timely postnatal check-ups, substantial gaps remained in essential care components such as cord examination (73.5%) and counselling on newborn danger signs (73.3%). Marked geographic disparities were observed, with Tamil Nadu (82.7%) and Andhra Pradesh (71.9%) reporting high QPNC utilisation, whereas Nagaland (<9%), Bihar, Uttar Pradesh, and several northeastern states performed poorly. At the district level 46 districts reported QPNC below 20%, mainly in Bihar and Nagaland. QPNC utilisation was comparatively higher in private facilities and higher-tier public institutions. Maternal education (AOR=1.08), wealth status (AOR=1.20), health insurance (AOR=1.24), media exposure (AOR=1.25), ≥4 antenatal care visits (AOR=1.79), and institutional delivery (AOR=17.71) increased the likelihood of receiving QPNC. Larger household size (AOR=0.93), healthcare access barriers (AOR=0.92), and caesarean delivery were associated with lower QPNC utilisation, while vaginal delivery was associated with higher odds of QPNC compared with caesarean delivery (AOR=1.18). CONCLUSION: Substantial socio-economic, institutional, and geographic disparities persist in QPNC utilisation across India. Improving continuity and completeness of PNC requires strengthening maternal education, financial protection, healthcare infrastructure, and counselling support, particularly in underserved regions. Targeted district-level and facility-level interventions are essential to improve maternal and newborn health outcomes.